PULSE, BLOOD OXYGEN AND BODY TEMPERATURE MEASUREMENT SYSTEM WITH INTERNET DATA MONITORING. CONSTRUCTION, INSTALLATION, CONFIGURATION SYSTEM PROGRAMMING - Ioana Laura ALEXANDRESCU; Ioan Marius ALEXANDRESCU (Carpathian Journal of Electrical Engineering)
The vision of creating this device was to ease the work of the people who would be responsible for the physical recording of the temperature of the people in an enclosure or a specific space, such as a medical office, for example, the pulse and the amount of oxygen in the blood by replacing the human resource with a device that takes all three with the help of sensors and not only that, it sends the data taken by them to some tables in the related database, after which it creates statistical graphs with them. Pulse, blood oxygen and body temperature measurement system with internet data monitoring has in the component sensors MLX90614 for remote body temperature recording, sensor that was connected to ESP32 microcontroller, using I2C communication protocol and MAX30100, which I used to measure pulse and blood oxygen level (SpO2), being connected to another microcontroller, Arduino Uno, also via I2C. What has been measured is displayed on an LCD2004, and the data is transmitted wireless to the local server, in the database created in MySQL.